2022
DOI: 10.1002/adma.202109952
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Doping Effect Leads to Ultrahigh Average Thermoelectric Power Factor in Cu3SbSe4‐Based Composites

Abstract: the dimensionless figure of merit zT = PF•T/κ = α 2 σT/(κ e + κ L ), where α, σ, T, κ e , and κ L are the Seebeck coefficient, electrical conductivity, absolute temperature, and electronic and lattice contributions to the total thermal conductivity, respectively. [3] PF denotes the TE power factor that characterizes electrical transport performance. In practice, the average power factor (PF avg ) is directly proportional to the output power density of TE devices. [4] Therefore, for practical application, a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 59 publications
(111 reference statements)
0
40
0
Order By: Relevance
“…10 In the past decades, a number of methods were carried out to increase the PF and PF ave , including adjusting the carrier concentration (n) and optimization of electronic band engineering, which were mainly achieved by doping. 11−15 Recently, we found that ternary copper-based tetrahedral structure compounds are deemed to be very promising TE materials due to their make of nontoxic constituent elements (tellurium-free) and excellent performance, such as Cu 3 SbSe 4 8,13 and Cu 2 SnSe 3 16,17 to name but a few. Among them, the Cu 2 GeSe 3 compound has attracted the increasing attention of researchers in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In the past decades, a number of methods were carried out to increase the PF and PF ave , including adjusting the carrier concentration (n) and optimization of electronic band engineering, which were mainly achieved by doping. 11−15 Recently, we found that ternary copper-based tetrahedral structure compounds are deemed to be very promising TE materials due to their make of nontoxic constituent elements (tellurium-free) and excellent performance, such as Cu 3 SbSe 4 8,13 and Cu 2 SnSe 3 16,17 to name but a few. Among them, the Cu 2 GeSe 3 compound has attracted the increasing attention of researchers in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a larger PF ave value is more suitable for obtaining a higher output power in practical applications . In the past decades, a number of methods were carried out to increase the PF and PF ave , including adjusting the carrier concentration ( n ) and optimization of electronic band engineering, which were mainly achieved by doping. …”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the strategies that are used to improve the performance of thermoelectric (TE) materials fall into two categories. One is to aim to improve the power factor PF via carrier concentration optimization, valence band convergence, , crystal structure modulation, , density of state (DOS) resonance, and energy filtering , and the other focuses more on reducing the lattice thermal conductivity κ lat by various approaches such as alloying, , discordant atoms, , nanostructuring, and twinning …”
Section: Introductionmentioning
confidence: 99%
“…Here, σ, S , κ e , κ L , and T stand for electrical conductivity, Seebeck coefficient, electronic and lattice thermal conductivity, and the absolute temperature, respectively . The high zT performance can be obtained by either increasing the power factor (PF = σ S 2 ) or reducing thermal conductivity. , For the purpose of promoting TE performance, the electrical properties can be promoted by carrier concentration optimization and energy band engineering , while lattice thermal conductivity can be suppressed by strengthening phonon scattering through defects , and boundaries and nanostructuring. , However, due to the strong coupling between σ, S , and κ, it is difficult to optimize these parameters simultaneously to obtain high zT values.…”
Section: Introductionmentioning
confidence: 99%